Changes in dietary intake improve glycemic control following a structured nutrition therapy during Ramadan in individuals with type 2 diabetes. (December 2021) - Mohd Yusof, Barakatun-Nisak; Hasbullah, Farah Yasmin; Mohd Shahar, Aainaa Syarfa; Omar, Noraida; Abu Zaid, Zalina; Mukhtar, Firdaus; Liu, Rachel Xin Yi; Marczewska, Agnieszka; Hamdy, Osama
Summary: Background and aims: It is unknown whether dietary modifications during Ramadan could influence glycemic control in diabetes. This study assessed dietary intake following structured Ramadan nutrition therapy and determined the association between changes in dietary intake and glycemic control parameters in patients with type 2 diabetes. Methods: This was an 8-week, parallel-group, non-randomised study of 60 type 2 diabetes patients who opted for structured Ramadan Nutrition Therapy (sRNT; n = 38) or standard care (SC; n = 22) group. The sRNT group received a structured Ramadan Nutrition Plan incorporated with diabetes-specific formula throughout the study, while SC received standard nutrition care. The 3-day food records assessed dietary intake at three-time points. Results: At baseline, dietary characteristics were comparable; both groups had macronutrient intakes within the recommended range, but inadequate intakes of fiber and 11 essential micronutrients. After 8 weeks, the sRNT group significantly reduced intakes of carbohydrate, dietary glycemic index, glycemic load, and increased percentage of total energy intake from protein, fiber, pyridoxine, vitamin C, vitamin D, calcium, and chromium compared with the SC group. In the sRNT group, compliance to diabetes-specific formula predicted changes in HbA1c (p = 0.024), while fiber intake predicted fasting plasma glucose (p = 0.035), after adjusting for age, sex, weight changes and other dietary variables. Conclusion: Intakes of certain nutrients improved significantly in sRNT group after 8 weeks of receiving a structured Ramadan Nutrition Plan compared to the standard care. The structured Ramadan Nutrition Plan with the incorporation of diabetes-specific formula significantly improved glycemic control and dietary adequacy during Ramadan fasting. Highlights: Structured RNP may benefit T2D patients who observe Ramadan fasting. Structured RNP improved intakes of 3 macronutrients and 5 micronutrients. Structured RNP with incorporation of DSF improved glycemic control of T2D patients.